A novel sodium-ion supercabattery based on vacancy defective Ni–Co–Mn ternary perovskite fluoride electrode materials. Issue 25 (21st June 2021) - Yan, Tong; Ding, Rui; Huang, Yongfa; Ying, Danfeng; Tan, Caini; Huang, Yuxi; Yang, Feng; Sun, Xiujuan; Gao, Ping; Liu, Enhui
Abstract : Proposal of a new concept of sodium-ion supercabatteries based on a novel vacancy defective Ni–Co–Mn ternary perovskite fluoride K0.71 Ni0.12 Co0.41 Mn0.47 F2.77 /rGO anode and an activated carbon/Na3 V2 (PO4 )2 O2 F hybrid cathode. Abstract : In this work, we have proposed a new concept of sodium-ion supercabatteries ( i.e., sodium-ion capacitors/batteries, SICBs) based on a novel vacancy defective Ni–Co–Mn ternary perovskite fluoride K0.71 Ni0.12 Co0.41 Mn0.47 F2.77 /reduced graphene oxide ( i.e., KMF(244)/rGO) anode and a capacitor/battery (activated carbon/Na3 V2 (PO4 )2 O2 F, i.e., AC/NVPOF) hybrid cathode, which reduce the gap between sodium-ion capacitors (SICs) and sodium-ion batteries (SIBs). The KMF(244)/rGO anode, with the synergistic effect of Ni, Co, and Mn redox species and K/F vacancy defects, presents remarkable specific capacity, rate and cycle performance, showing pseudocapacitive-dominated conversion/intercalation dual mechanisms. Interestingly, the KMF(244)/rGO//AC/NVPOF SICBs exhibit superior performance to KMF(244)/rGO//AC SICs and KMF(244)/rGO//NVPOF SIBs, which largely benefits from the synergistic energy storage superiority of SICs and SIBs showing pseudocapacitive, capacitive, and faradaic behavior in electrochemical processes. To sum up, our study presents a novel concept of sodium-ion supercabatteries realized by using the vacancy defective Ni–Co–Mn ternary perovskite fluoride anode with pseudocapacitive-dominated conversion/intercalation dual mechanisms and an AC/NVPOF capacitor/battery hybrid cathode, providing new insight into developing advanced energy storage devices and in-depth understanding of the charge storage mechanisms.